IFRS 8 and value relevance: evidence from Turkish listed companies - KÜLAH, SEZER (My University, 2022)
The purpose of this study is to investigate the relation between IFRS 8 Operating Segments Standard and value relevance. To investigate the issue a dataset based on a total of 22 selected Borsa Istanbul companies are evaluated from the years 2005 to 2020. Totally, 291 firm year observations and two models are run using panel data analysis on Stata program. According to the results, there is positive relation between book value of equity per share and income per share over stock prices. Furthermore, income per share of a segment and book value of equity per share have positive effect on stock prices for the companies adopted IFRS 8 Operating Segments Standard. In this study, literature is summarized at the first part. At the second part, value relevance analyses are carried out over the companies adopted IFRS 8.

Bu çalışma, değer ilişkisi ve UFRS 8 faaliyet bölümleri standardı arasındaki ilişkiyi incelemektir. Araştırma için 2005-2020 yılları arasında Borsa İstanbul’da işlem gören toplam 22 firma seçilmiş ve veri seti oluşturulmuştur. Stata programında panel veri analizi kullanılarak toplam 291 gözlem oluşturulmuş ve analiz iki farklı modelde incelenmiştir. Sonuçlara göre, hisse başına özsermayenin defter değeri ile hisse başı gelir arasında hisse senedi fiyatları üzerinde pozitif bir ilişki vardır. Ayrıca, UFRS 8 faaliyet bölümleri standardını uygulayan firmalarda faaliyet bölümlerinin hisse başına özkaynak defter değeri ile hisse başı gelir arasında pozitif bir ilişki olup hisse senedi fiyatları üzerinde olumlu bir etkisi vardır. Bu çalışmada ilk bölümde literatür özetlenmiştir. İkinci bölümde ise UFRS 8 faaliyet bölümleri standardını uygulayan firmalar üzerine değer ilişkisi analizi yapılmıştır.
UFRS 8 ve değer ilişkişi: borsaya kote Türk firmalarından bulgular
Keywords: Sosyal ve Beşeri Bilimler; İşletme; Muhasebe; Muhasebe ve Denetim; Social Sciences and Humanities; Management; Accounting; Accounting and Control; Sosyal Bilimler (SOC); Ekonomi ve İş; İŞLETME; YÖNETİM; Social Sciences (SOC); ECONOMICS & BUSINESS; BUSINESS; MANAGEMENT; Karar Bilimleri (çeşitli); Genel Karar Bilimleri; Strateji ve Yönetim; Pazarlama; İşletme ve Uluslararası Yönetim; Genel İşletme, Yönetim ve Muhasebe; Sosyal Bilimler ve Beşeri Bilimler; Decision Sciences (miscellaneous); General Decision Sciences; Strategy and Management; Marketing; Business and International Management; General Business, Management and Accounting; Social Sciences & Humanities; IFRS 8; operating segments; value relevance; stock market; panel data; UFRS 8; faaliyet bölümleri; değer ilişkisi; borsa; panel veri